2002
DOI: 10.1097/00001199-200208000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances and Their Management in Patients with Brain Injury

Abstract: These discussions will hopefully assist in the decision-making processes of caregivers managing this unique group of persons with sleep difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Sleep problems following TBI can be secondary to a myriad of factors, including injury to brain structures responsible for sleep regulation [44,45], pain, co-morbid medical problems, side-effects of medications or secondary to psychiatric disorders [46]. Psychiatric disorders are common after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems following TBI can be secondary to a myriad of factors, including injury to brain structures responsible for sleep regulation [44,45], pain, co-morbid medical problems, side-effects of medications or secondary to psychiatric disorders [46]. Psychiatric disorders are common after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems in the immediate TBI period can be secondary to numerous factors: injury to sleep regulating centres [11], pain, comorbid medical problems, side effects of medications, or a symptom of a mood and/or anxiety disorder [12]. From this report, new onset anxiety disorder with generalized anxiety features that developed for the first time after TBI (GADGMCC) was the most consistent correlate of various specific sleep disturbances and of the global measures of sleep problems (Sleep Problems Index 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…4 A variety of mechanisms have been proposed to explain how TBI might increase the risk for sleep problems, including physical pain, disrupted neural networks, and emotional trauma. 4,5 The existing literature on sleep in childhood TBI is equivocal. Several studies have shown more sleep disturbance in children with TBI than in healthy children or in those with orthopedic injuries (OIs).…”
Section: Introductionmentioning
confidence: 99%